Presentism, atemporality and time's way - Leftow, B (Philosophy Documentation Center, 2018)
After defining presentism, I consider four arguments that presentism and divine atemporality are incompatible. I identify an assumption common to the four, ask what reason there is to consider it true, and argue against it.